Choral event-art space through the prism of today - Vasilyeva, Oksana (Professional Art Education, 2024)
Object. The aim of this article is to analyze the modern choral event-art space from the perspective of recent scientific research and to characterize the artistic events existing in choral practice.Methods & methodology. The study employs traditional theoretical methods of analyzing scientific literature, the method of analogy to identify similar features of choral artistic events with event phenomena in other areas of social life, as well as generalization and comparison of choral event-art forms characteristic of modern choral art and their classification.Results. The research results indicate the widespread use of the concepts "art space," "world of contemporary art," "art world," and "field of art" in cultural and scientific contexts. The essence of the definitions "space," "art space," and "event-art space" in art and cultural studies has been defined. It has been established that the modern musical and artistic environment is transforming into an event-art space, characterized by a great variety of forms and types of artistic events. The category "event" is revealed as a clearly planned social event in the fields of science, culture, and art, which resonates within society. The author emphasizes the target orientation of events towards specific age or social audiences. These events encompass various forms of art, such as exhibitions, installations, performances, multimedia shows, and other forms of creative expression.The modern choral event-art space has been characterized, including festivals, city celebrations, competitions, ceremonial events, concerts, educational activities, master classes by leading choral experts, seminars, and Olympiads.Forms of choral events have been analyzed using examples such as the All-Ukrainian Mykola Leontovych Choral Competition, the All-Ukrainian Two-Stage Choral Art Competition named after Mykhailo Krechko, the Pavlo Muravsky International Choral Competition, and the Dmytro Bortniansky International Competition. The distinctive features of choral festivals, performances, choral flash mobs, choral marathons, choral assemblies, and shows have been identified. Illustrative examples of these events include the "Mykola Leontovych Choral Assemblies," the Kharkiv International Choral Festival "PalkinFest," the show "Battle of the Choirs," and others.Conclusions. Thus, the choral event-art space becomes an important element of contemporary culture, combining creativity, innovation, and sociocultural impact. Its development and research open new possibilities for choral art and significantly expand its audience. The latest choral events are dynamic and innovative, integrating music and technology. Such innovative approaches contribute to creating captivating and unique musical experiences.
Keywords: choral art; choral concerts; festivals; choral flash mob; choral show; choral marathon